Use of Multislice CT for Investigation of Occult Geriatric Hip Fractures and Impact on Timing of Surgery. (21st January 2019) - Williams, John; Allen, Felix; Kedrzycki, Marta; Shenava, Yathish; Gupta, Renu
Introduction: The National Institute of Health and Clinical Excellence guidelines in the United Kingdom recommend magnetic resonance imaging (MRI) as the first-line investigation for radiographically occult hip fractures, if available within 24 hours. In our department, however, multislice computerized tomography (MSCT) is instead used as a first-line investigation due to significant delays associated with obtaining MRI. Our aim was to determine the validity and practicality of MSCT for diagnosis of occult hip fractures and its impact on timing of surgery. Materials and Methods: We retrospectively analyzed medical records and imaging for consecutive patients who underwent MSCT to investigate occult hip fractures between January 2014 and October 2016. We reviewed subsequent imaging and reattendances for patients with negative MSCT to exclude initially missed fractures. Results: Two hundred six patients underwent MSCT to investigate occult hip fracture during the study period. Hip fractures were identified in 59 patients, comprising 35 (59.3%) subcapital, 12 (20.0%) intertrochanteric, 8 (13.6%) transcervical, and 4 (6.8%) basicervical fractures. One missed hip fracture was identified: a patient with a negative MSCT was further investigated with MRI that demonstrated acute subcapital hip fracture. Multislice computerized tomography was obtained within 24 hours of initial radiograph in 145 (70.4%) patients. A total of 44.5% of occult hip fractures had surgery within the nationally recommended 36 hours of admission (hospital average for all hip fractures was 76.4% over the same period). Discussion and Conclusions: Multislice computerized tomography is a pragmatic approach to investigate the majority of occult hip fractures in a timely manner and minimize associated delay to surgery. However it cannot completely exclude the diagnosis, especially in abnormal anatomy. The lack of a true gold standard comparison (ie, MRI) means a true sensitivity and specificity cannot be calculated, although can be cautiously estimated by lack of subsequent reattendance or investigation. Further prospective randomized CT versus MRI trials are required.